Methods of Achieving Socialism: Georgi Plekhanov's Thought as a Case Study (Raparin Journal of Humanities (RJH), 2025)
The realization of socialism, how to achieve it, and the tools of achieving socialism is differ among neo-Marxist thinkers in the twentieth century. The most two obvious trends for achieving socialism are: revolution, and the democratic reform. The thinkers of revolutionary socialism are emphasize rapid and radical change to achieve socialism through the use of armed and violent revolutionary tools, while the thinkers of  Social Reform & Social Democracy emphasize on adopting via peaceful way without violence. Social democratic thinkers are divided into two distinct trends: revisionism and determinism. Revisionism emphasizes parliamentary reform, using of democratic ways and elections to achieve workers' rights. The determinist trend emphasizes on the role of history and Marx's historical materialism in achieving socialism, according to the determinists socialism is an inevitable historical stage that occurs after the collapse of capitalism and the turning of society. The Orthodox Marxists such as Kautsky and Plekhanov are among this trend's thinkers. Plekhanov, the Socialist leader in the Soviet Union, emphasized the realization of socialism through peaceful away without armed revolution. For Plekhanov, history played a major role in determining individuals and societies to realize the aspirations of history. He also believed that individuals have a passive role compare to the society, furthermore art and artistic aesthetics play a fundamental role in class consciousness and the subsequent realization of socialism, and the whole process of transition to socialism for Plekhanov occurs during the historical development of society and according to Marx's historical materialism.